2001
DOI: 10.1097/00003226-200101000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Morphological Characteristics of the Human Corneal Endothelium in Relation to Age, Gender, and Ethnicity in Cataract Populations of South Asia

Abstract: In a total sample of 1,235 eyes distributed evenly in three cataract patient populations of south Asia, we found statistically significant differences of corneal endothelial cell densities of cell size variability and cell hexagonality between sexes and ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
3
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 14 publications
9
43
3
10
Order By: Relevance
“…[15][16][17][18][19][20] When compared with mean ECD values reported for children (3400-4300 cells/mm 2 ) and for elderly eyes (2324-3175 cells/mm 2 ), a clear trend of decreasing mean ECD with advancing age is observed. [9][10][11]15,17,[21][22][23][24][25] Consistent with the majority of other published reports, there was no significant difference in mean ECD based on gender in this study. 5,9,16,17,26,27 With regards to the reliability and repeatability of the NAVIS endothelial analysis system, automated endothelial analysis often fails to correctly identify endothelial cell borders.…”
Section: Discussionsupporting
confidence: 91%
“…[15][16][17][18][19][20] When compared with mean ECD values reported for children (3400-4300 cells/mm 2 ) and for elderly eyes (2324-3175 cells/mm 2 ), a clear trend of decreasing mean ECD with advancing age is observed. [9][10][11]15,17,[21][22][23][24][25] Consistent with the majority of other published reports, there was no significant difference in mean ECD based on gender in this study. 5,9,16,17,26,27 With regards to the reliability and repeatability of the NAVIS endothelial analysis system, automated endothelial analysis often fails to correctly identify endothelial cell borders.…”
Section: Discussionsupporting
confidence: 91%
“…They suggested that this might account for a lower incidence of aphakic bullous keratopathy in Japanese than in Americans. Snellingen and associates 38 proposed that there is a need for further interethnic studies of corneal endothelium to determine whether certain ethnic groups are more prone to surgical trauma.…”
Section: ⅲ Corneamentioning
confidence: 99%
“…Sadece endotel hücre yoğunluğunda azalma olduğunu göste-ren çalışmaların yanında, DK ve hegzagonalite üze-rinde etkisinin de olduğunu gösteren çalışmalar bulunmaktadır. 10,20 PES'li hasta grubunda glokom varlığının etkisinin değerlendirildiği bir çalışmada endotel hücre yoğunluğunda fark yok iken, glokomu olan PES hastalarında DK ve hegzagonalitede bozulma olduğu gösterilmiştir. 21 PES'nin endotel hücre yoğunluğu, DK ve hegzagonaliteye etkisinin olup olmadığını incelediğimiz bu çalışmada, sadece endotel hücre yoğunluğu üzerinde anlamlı bir etki gösterildi.…”
Section: Discussionunclassified
“…12 Snellingen ve ark.,Hindistan, Bangladeş ve Nepal'de yürüttükleri çalışmada, endotel hücre yoğunluğunda etnik farklılık üzerinde durmuşlardır. 20 Bildirilen endotel hücre yoğunluğu arasındaki geniş dağılım, etnik farklılıkların endotel yapısını etkilediğini düşündürmektedir.…”
Section: 23unclassified